Contrasting latitudinal patterns in phylogenetic diversity between woody and herbaceous communities - Massante, Jhonny C; Götzenberger, Lars; Takkis, Krista; Hallikma, Tiit; Kaasik, Ants; Laanisto, Lauri; Hutchings, Michael J; Gerhold, Pille (Scientific reports, 2019)
Although many studies have shown that species richness decreases from low to high latitudes (the Latitudinal Diversity Gradient), little is known about the relationship between latitude and phylogenetic diversity. Here we examine global latitudinal patterns of phylogenetic diversity using a dataset of 459 woody and 589 herbaceous plant communities. We analysed the relationships between community phylogenetic diversity, latitude, biogeographic realm and vegetation type. Using the most recent global megaphylogeny for seed plants and the standardised effect sizes of the phylogenetic diversity metrics 'mean pairwise distance' (SESmpd) and 'mean nearest taxon distance' (SESmntd), we found that species were more closely-related at low latitudes in woody communities. In herbaceous communities, species were more closely-related at high latitudes than at intermediate latitudes, and the strength of this effect depended on biogeographic realm and vegetation type. Possible causes of this difference are contrasting patterns of speciation and dispersal. Most woody lineages evolved in the tropics, with many gymnosperms but few angiosperms adapting to high latitudes. In contrast, the recent evolution of herbaceous lineages such as grasses in young habitat types may drive coexistence of closely-related species at high latitudes. Our results show that high species richness commonly observed at low latitudes is not associated with high phylogenetic diversity.
Keywords: rostliny; Plants; tropické klima; Phylogeny; biodiverzita; vývoj rostlin; fylogeneze; Tropical Climate; Plant Development; Biodiversity